PENINGKATAN KUANTITAS, KUALITAS, DAN KONTINUITAS INDUSTRI KERTAS HANDMADE - Widowati, Widowati; Retnoningsih, Amin; Prajanti, Sucihatiningsih Dian Wisika (Universitas Negeri Semarang, 2017)
The problem of small handmade paper industry comes from the not yet optimal quan- tity and quality of products that ultimately impact on continuity. The production of this paper is subject to weather, material limitations and handmade paper making techniques that ultimately affect product continuity. Consumers of handmade paper generally craftsmen also want pa- per that varies in the manufacture of paper products. The objective of the activity is to improve the ability of small industries to improve the quantity and quality of handmade paper and hand- made paper products. Implementation of science and technology in making handmade paper pro- duces 6 variants of paper made from single raw material or mixture of mendong, grass, waste paper and banana debog with synthetic and natural staining and pattern using various forms of leaves. The use of cutting tools that vary and sharp also has produced 6 types of paper boxes made from handmade paper, including a form that is quite difficult to make such as round, oval or heart shape. The manufacture of products for a certain amount has been mastered so that small industries are able to accept orders in a relatively quick time according to the needs of consumers